An investigation of the laser-induced zircon 'matrix effect' - Marillo-Sialer, E.; Woodhead, J.; Hanchar, J.; Reddy, Steven; Greig, A.; Hergt, J.; Kohn, B. (Elsevier Science BV, 2016)
This study aims to improve our understanding of the current limitations to high-precision U-Pb analysis of zircon by LA-ICP-MS by investigating the underlying causes of variation in ablation behaviour between different zircon matrices. Multiple factors such as: the degree of accumulated radiation damage, trace element composition; crystal colour; and crystallographic orientation are all systematically investigated. Due to the marked decrease in elastic moduli of natural zircon crystals with increasing radiation damage, the accumulation of this damage is the dominant factor controlling the rate of ablation for partially damaged to highly metamict zircon samples. There are slight differences, however, in ablation behaviour between highly crystalline matrices that cannot be attributed solely to differences in the degree of accumulated radiation damage. These differences are associated with structural weakening (i.e., decrease in elastic moduli and overall lower mechanical resistance) caused by an increasing degree of cation substitution in some of the zircon samples. Effects of crystallographic orientation and of crystal opacity (i.e., colour) on ablation behaviour are negligible compared to the combined influences of accumulated radiation damage and trace element substitution into the zircon structure. Experiments performed on natural and annealed zircon grains reveal that the reduction in ablation rates observed for the treated samples compared to the untreated grains is proportional to the degree of structural reconstitution achieved after annealing. Thermal annealing of natural zircon at temperatures >1000 °C results in much more uniform ablation characteristics. This 'homogenisation' of ablation behaviour between zircon matrices produces a decrease in the laser-induced matrix effects and subsequent improvement in the accuracy of 206Pb/238U ratio determinations by LA-ICP-MS.